ANTESEDEN DAN KONSEKUEN BERBAGI PENGETAHUAN DALAM PENINGKATAN KINERJA ORGANISASI - Setyo Hartono, R. Djoko (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2014)
Knowledge sharing is a process in which individuals exchange their knowledge (implicit and explicit) and they create new knowledge together. Knowledge is an valuable source for organizations that cause to survive in competitive environment and can be used to achieve competitive advantage. Knowledge can be available to individuals and organizations, therefore, there must exit conditions in the organization that people be able to share their knowledge with other individuals. In such situation, organizations can improve employees performance and also organizations performance. This paper explores the antecedents and consequences knowledge sharing. This study argued that social interaction ties, shared vision and trust should be associated with knowledge sharing. Next, the conceptual relationship between knowledge sharing and individual performance, organizational performance, and organization competitive has been established.